Attitudes of higher education professors towards e-learning and its impact on the quality of educational service “A case study of the Faculty of Social Sciences - Larbi Ben Mehidi University Oum El Bouaghi - hadji, abdelhakim; denbri, lotfi (Journal of Social Sciences and Humanities, 2024)
Adopting management plans open to the structure of a changing environment and the trend towards digitalization of institutional processes has become an inevitable necessity imposed on the higher education sector in particular, so that e-learning takes a place central in the educational formula, transcending the traditional stereotype of the educational process in order to approach the virtual experience of higher education and apply quality of service standards, according to this. Cognitive framework: The current field study aimed to test the relationship and impact between teachers' attitudes towards online learning and the quality of educational service Using the descriptive approach and the global survey method with around 70 teachers from the Faculty of Social Sciences of Larbi Ben M'hidi University, Oum El Bouaghi, and using the results of the statistical software package spss23, the study managed to confirm the existing hypothesis through the value of the estimated Pearson correlation coefficient at (0.794)..